High-voltage pulse crushing and physical separation of polycrystalline silicon photovoltaic panels. (15th August 2018) - Akimoto, Yuta; Iizuka, Atsushi; Shibata, Etsuro
Highlights: High-voltage pulse crushing technology was applied to photovoltaic panel treatment. Crushed products were separated by sieving and dense medium separation. Glass was in the 45–850 μm fraction and purified by dense medium separation. Ag was highly condensed (3000 mg/kg) in the sieved products. The power cost for high-voltage pulse crushing was estimated. Abstract: High-voltage pulse crushing technology combined with sieving and dense medium separation was applied to a photovoltaic panel for selective separation and recovery of materials. The panel was first separated into glass and back sheet layers by high-voltage pulse crushing through microexplosions or shock waves transmitted in the Al electrode and Si substrate (primary crushing step). Then the glass and bus-bar electrode could be separated from the encapsulant by high-voltage pulse crushing of the glass layer. The bus-bar electrode of the back sheet layer could also be separated by further high-voltage pulse crushing. After sieving the products obtained from the secondary crushing step of the glass layer, glass was mainly distributed in the size fraction range of 45–850 μm with a small amount of Si powder. However, purification of the glass (removal of Si powder) could be achieved by dense medium separation at a specific gravity of 2.4. Base metals, such as Cu, Sn, and Pb could be recovered in the large size fraction (1.0–8.0 mm). Ag used in the finger and bus-bar electrodes was highly condensed in the sieved product fraction with sizes of less than 20 μm, 2.0–4.0, and 4.0–8.0 mm, and its content exceeded 3000 mg/kg. However, the amount of Ag in these fractions represented only 33.2% of the total amount of Ag in the panel. Thus, to increase the Ag recovery ratio, other separation methods will be needed. We confirmed that dense medium separation at a specific gravity of 3.0 could achieve Ag condensation from the Si and glass, and that this represents a promising option for enhanced Ag recovery from crushed products.